Remoção de fósforo do esgoto tratado utilizando lodo de ETA e casca triturada de ovo como adsorvente - Ribeiro, Ivan Célio Andrade (2017)
Inadequate disposal of effluents rich with phosphorus (P) represents a serious environmental risk worldwide due to the eutrophication of water bodies. This process stimulates the multiplication of algae and macrophytes in the aquatic environment. In addition to changing the taste and odor of water, some algae can release toxins that cause serious human health problems. The present work had as objective to study and evaluate the phosphorus removal process present in the effluent from the biological treatment of the wastewater treatment plant from Federal University of Lavras (WWP / UFLA), with powered chicken eggs shell and by the sludge generated at the water treatment plant of the same university. Leaching columns were prepared with 0.047 m in diameter and 0.50 m in height in order to evaluate the adsorption and mobility of P. In addition, phosphor adsorbing bags (PAB), building with filter paper, were tested for phosphorous removal in a jar test apparatus; And up-flow filters, 0.047 m in diameter and 0.15 m in height, containing as filter medium a layer of sludge between two sawdust 0,05 m thick. The sludge from the drainage in drying beds of the effluent from the cleaning of the filters and the decanter of the water treatment plant, which uses ferric chloride as a coagulating agent. The eggshells were available by the Santo Antônio aviary. The residues were cleaned, air-dried, hand-ground and then homogenized after sieving 0.425 mm. The results allowed concluding that: a) the sorption isotherms fitted well to the experimental data and the best adjustments were obtained using the Freundlich model for WWA sludge and Langmuir for chicken egg crust; b) the values of maximum sorption capacity of P for the sludge and the crushed eggshell were 7.30 and 20.4 mg g-1, respectively; c) it was estimated that the total removal of P using phosphorus adsorbent bags (PAB) containing 10, 25 and 50 g of ETA sludge was, respectively, 186, 155 and 133 h, for the removal of all this Nutrient contained in one liter of WWP/ UFLA effluent; d) the leaching column constituted by the sludge presented a retardation factor of 576 pore volume; d) with regard to chicken egg crust, it was not possible to calculate the retardation factor due to the obstruction of the pores of the column of this residue; e) for the SAPs used in the proportion of 10, 25 and 50 g of ETA sludge per liter of treated effluent, it was estimated that it would take about 186, 155 and 133 hours for the total removal of that nutrient; f) SAPs filled with chicken eggshell promoted a maximum removal ranging from 30 to 35% of phosphorus, and it was not possible to adjust an equation that related the solid-solution contact time and efficiency in the removal of P; g) the crude husk of chicken hens, in nature, presented concentrations of available and total P equal to 6.9 and 737mg kg-1 and, after using this material in columns to Phosphorus retention, these values released to 8, 3 and 909 mg kg-1; h) the Natural sludge presented concentrations of available and total P equal to 0.0 and 511.0 mg kg-1e, after using this material in phosphorus retention columns, these values increased to 1,7 e 712.0 mg kg-1; i) the increase in available phosphorus content in evaluated residues, after used in columns of retention, represents an indication of possible agricultural use, as a source of natural nutrient for agricultural crops.